Cross‐sectional differences in symptomatic presentation and cognitive performance among participants with LATE‐NC compared to FTLD‐TDP: Neuropsychology: Neuropsychological correlates of pathology — Novel and standard cognitive markers of disease. (7th December 2020) - Teylan, Merilee; Mock, Charles; Gauthreaux, Kathryn; Culhane, Jessica E.; Chen, Yen‐Chi; Chan, Kwun Chuen Gary; Kukull, Walter A.; Nelson, Peter T; Katsumata, Yuriko
Abstract: Background: Transactive response DNA‐binding protein 43 (TDP‐43) is misfolded and aberrantly phosphorylated in FTLD‐TDP. It is also the key proteinopathic feature in limbic‐predominant age‐related TDP‐43 encephalopathy neuropathologic change (LATE‐NC). There has been some controversy as to the similarities and differences between FTLD‐TDP and LATE. We examined how the symptomatic presentation and cognitive performance compare between autopsy‐confirmed LATE‐NC and FTLD‐TDP. Method: Participants with LATE‐NC or FTLD‐TDP were identified at autopsy using data from the National Alzheimer's Coordinating Center Neuropathology Data Set v10. Participants were excluded if they had other rare neuropathologic diseases or had their last clinic visit greater than 36 months from their date of death. Presence of cognitive, behavioral, and motor symptoms were compared among those with a dementia diagnosis at their last visit. Linear regression analyses with generalized estimating equations were run to test for mean differences between the two groups on five cognitive domain z‐scores (episodic memory, attention/working memory, executive function, semantic memory, global composite score) calculated from neuropsychological test scores at their last visit. Models were stratified based on global CDR score (CDR=0.5‐1, 2‐3) and adjusted for neuropsychological test battery, age at death, sex, years of education, Alzheimer's disease neuropathologic change, presence of Lewy bodies, and presence of microinfarcts. Result: We identified 233 LATE‐NC and 86 FTLD‐TDP participants. LATE‐NC participants were older at death and more likely to be an APOE ε4 carrier than those with FTLD‐TDP. Dementia participants with LATE‐NC were less likely to demonstrate language impairment, apathy, disinhibition, and personality changes, but were more likely to have visuospatial impairments, visual hallucinations, and delusions compared to FTLD‐TDP participants. Examining the differences in mean cognitive domain z‐scores, participants with LATE‐NC and a global CDR score of 0.5‐1 performed significantly better in the language domain compared to those with FTLD‐TDP. Significant differences in mean z‐scores were not observed among other cognitive domains, or among participants with a global CDR score of 2‐3. Conclusion: In this sample, there were symptomatic differences between LATE‐NC and FTLD‐TDP among participants with dementia. Difference in the language domain could be detected in mild stages of impairment through neuropsychological test scores.